(untitled) (Gilgameš, 2016)
In Italy, as in the rest of the Roman Empire, roman urban fortifications usually include walls and defensive moats. Unlike the walls, the moat is often hard to identify due to the urban stratification from the Middle Ages to the present day. However, combining archaeological evidence with the study of historical sources could lead to a real understanding of the ancient defense systems. This paper aims to give a brief survey of the evidences, by comparing different Northern Italy realities.